MANAJEMEN SARANA PRASARANA SEKOLAH DASAR DALAM MENJAMIN KEBERLANJUTAN FASILITAS BELAJAR - Agustian, Mochammad Candra Agustian; Ai Nuryati; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational facilities and infrastructure are crucial factors in achieving effective and efficient educational goals, as mandated by the Constitution and the Law on the National Education System. However, current realities indicate existing disparities in educational facilities that hinder the teaching and learning process. This study aims to analyze the urgency, eligibility standards, and management mechanisms of educational facilities and infrastructure in schools. The research method employed is qualitative with a literature review (library research) approach, where data were collected from various primary and secondary sources, classified, and interpreted to form comprehensive conclusions. The results indicate that adequate, inclusive, and disability-friendly facilities and infrastructure, in accordance with Minister of Education, Culture, Research and Technology Regulation (Permendikbudristek) No. 22 of 2023, can significantly increase student learning motivation. Furthermore, the management of these facilities requires a systematic strategic approach, including priority-based planning, task organization, and administrative supervision to prevent mismanagement. The study concludes that a management cycle consisting of seven stages—ranging from needs analysis to reporting—is vital to ensuring the availability and sustained quality of educational facilities to meet national education standards.